2015
DOI: 10.1051/0004-6361/201423518
|View full text |Cite
|
Sign up to set email alerts
|

Measuring star formation with resolved observations: the test case of M 33

Abstract: Context. Measuring star formation on a local scale is important to constrain star formation laws. It is not clear yet, however, whether and how the measure of star formation is affected by the spatial scale at which a galaxy is observed. Aims. We wish to understand the impact of the resolution on the determination of the spatially resolved star formation rate (SFR) and other directly associated physical parameters such as the attenuation. Methods. We carried out a multi-scale, pixel-by-pixel study of the nearb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 89 publications
11
59
0
Order By: Relevance
“…In the recent study Boquien et al (2015) came to the same conclusions based on more data in different wavelengths including FUV as well. Analysing the spatial distribution of CO/Hα peaks in M 33 Schruba et al (2010) established that the scaling relation between gas and star formation rate surface density observed at large scales does not have its direct origin in an instantaneous cloud-scale relation.…”
Section: Introductionsupporting
confidence: 56%
“…In the recent study Boquien et al (2015) came to the same conclusions based on more data in different wavelengths including FUV as well. Analysing the spatial distribution of CO/Hα peaks in M 33 Schruba et al (2010) established that the scaling relation between gas and star formation rate surface density observed at large scales does not have its direct origin in an instantaneous cloud-scale relation.…”
Section: Introductionsupporting
confidence: 56%
“…In early-type galaxies, this quantity drops to less than 15% Calzetti (2001). In M33, Boquien et al (2015) found 75% of star formation in a H , with only 25% in the infrared. In Figure 9, we combine our synthetic FUV flux maps to examine the fraction of obscured star formation within the PHAT footprint and compare them with corresponding observed data from GALEX and Spitzer.…”
Section: Obscured Flux and Star Formationmentioning
confidence: 94%
“…A number of studies have examined how interpreting the observed galaxy flux is affected by some of these assumptions (e.g., Lee et al 2009;Chomiuk & Povich 2011;Weisz et al 2012;Wilkins et al 2012;Johnson et al 2013;Boquien et al 2014;Simones et al 2014, among many others). In a recent paper, Boquien et al (2015) analyzed the scale dependence of SFR tracers. They found broad agreement between tracers on ∼1 kpc scales, presumably because variations between regions of active star formation and diffuse emission (i.e., from older stellar populations) have averaged out.…”
Section: Introductionmentioning
confidence: 99%
“…deg. The PACS 70 µm image was obtained as a follow-up open time cycle 2 programme, on 25 June 2012 in two orthogonal directions and five repetitions to achieve better sensitivity (Boquien et al 2015). The PACS reduction was performed using the mapmaking software Scanamorphos (Roussel 2013) as described in Boquien et al (2011).…”
Section: Herschelmentioning
confidence: 99%